CLASSIFICATION OF BUILDING STONES OF THE FRANGOKASTELLO CASTLE, SFAKIA, CRETE - Cheimonas, Th.; Manoutsoglou, E.; Stavroulaki, M.; Skoutelis, N. (Bulletin of the Geological Society of Greece, 2016)
Frangokastello is a medieval castle which was built by the Venetians in 1371-74 in a narrow coastal zone at the southeastern part of the White Mountains, approximately 12 km east of Chora Sfakion. The region around Frangokastello characterized by a strong morphological relief, which was formed by activity of normal faults striking E-W, NNESSW and NNW-SSE. The region of interest has covered at the surface from sequences mainly marine sediments of Τortonian, Low Pliocene and Lower Pleistocene. From the Middle Pleistocene multiple alluvial fans have been cover the alpine basement of the region which consists from metamorphic rocks of the Plattenkalk Group, Trypali Unit and Phyllite Quartzite Series as well the youngest in age formations. Rounded and angular fragments of rock materials from alpine and post alpine formations transported and deposited within the various parts of alluvial fan which had deposited over the Frangokastello formation, constituted the building stones for the construction of the castle. The microclimate of the region and the intense tectonic activity associated with relatively high rates of uplift of the tectonic segments in the region, has critically affect not only the static of the castle but also the resistance from the weathering of building stones after physical dismantling large parts of the binding cement and surface from outer wall. On the basis of the above, the objective of this work is initially the collection of bibliographic data related to the stratigraphy and tectonics of the region. The results obtained, combined with the results from counting and statistical processing of various lithological types of building materials of the castle can be considered input data to form static models, in the framework of proposals for maintenance and restoration of the monument.